'Was it worth it?' Intrathecal analgesia for cancer pain: A qualitative study exploring the views of family carers. (January 2018) - Patel, Nishi; Huddart, Melanie; Makins, Helen; Mitchell, Theresa; Gibbins, Jane L; Graterol, Juan; Stevens, Deborah; Perkins, Paul
Background: Intrathecal drug delivery is known to reduce pain in patients where conventional systemic analgesia has been ineffective or intolerable. However, there is little information regarding the effects of intrathecal drug delivery on quality of life and function in those with advanced, incurable cancer. Aim: Retrospective exploration of the views of bereaved carers regarding the physical and psychosocial effects of external tunnelled intrathecal drug delivery in patients with advanced incurable cancer. Design: Thematic analysis of qualitative interviews with carers of deceased individuals who received percutaneous external tunnelled intrathecal drug delivery as part of their pain management, within two UK centres. Setting: A total of 11 carers were recruited from two UK Palliative Care centres. Family carers of adult patients who had received external tunnelled intrathecal drug delivery analgesia for cancer pain and had died between 6 and 48 months prior to contact were included. Carer relatives who were considered likely to be too vulnerable or who had lodged a complaint about treatment within the recruiting department or who had been treated directly by the interviewer were excluded. Results: In total, 11 interviews took place. The emerging themes were (1) making the decision to have the intrathecal – relatives described desperate situations with severe pain and/or sedation, meaning that the individual would try anything; (2) timing and knowing they were having the best – an increased access to pain and palliative care services, meant carers felt everything possible was being done, making the situation more bearable; (3) was it worth it? – the success of the external tunnelled intrathecal drug delivery was judged on its ability to enable the individual to be themselves through their final illness. Side effects were often considered acceptable, if the external tunnelled intrathecal drug delivery enabled improvements in quality of life. Conclusion: Carers perceived external tunnelled intrathecal drug delivery as most valuable when it improved quality of life towards the end of life, by reducing pain and side effects of conventional systemic analgesia to enable individuals 'to be themselves'. Under these circumstances, the carers judged significant side effects to be acceptable.